Prosthetic rehabilitation of a patient after a partial mandibulectomy - Goiato, Marcelo Coelho [UNESP]; Medeiros, Rodrigo Antonio de [UNESP]; Vechiato Filho, Aljomar José [UNESP]; Silva, Emily Vivianne Freitas da [UNESP]; Sônego, Mariana Vilela [UNESP]; Carvalho, Karina Helga Turcio de [UNESP]; Guiotti, Aimée Maria [UNESP]; Dekon, Stefan Fiuza de Carvalho [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Santos, Daniela Micheline dos [UNESP] (Elsevier B.V., 2015)
The treatment of orofacial tumors may cause facial deformities by losses of structures that affect basic functions, i.e. feeding, speech, and the reduction of patient self-steam. A white male patient was diagnosed with epidermoid cancer on the mandibular alveolar ridge with infiltration staging IV A. The patient was submitted to a mandibulectomy associated with a complete extraction of mandibular teeth. For rehabilitation, a conventional denture for the mandibular arch and a removable partial denture for the maxillary arch were fabricated. A correct occlusal adjustment and a satisfactory amount of alveolar bone was favorable for conventional dentures of the prostheses bases improve their retention and stability. After one year of follow-up, the patient was adapted to the prostheses, satisfied with their retention, and reported an improvement on his feeding. The prosthetic rehabilitation of patients after a partial mandibulectomy is essential for their self-steam. Conventional dentures may have their retention and stability improved if they are well fabricated, recorded and have a balanced occlusion. A correct occlusal adjustment and an adequate retention of the prostheses bases may improve their retention and stability. Patients without xerostomy and with a satisfactory amount of alveolar bone may have a favorable prognosis for conventional dentures.
Keywords: Denture; Epidermoid carcinoma; Mouth rehabilitation; Quality of life